1984
DOI: 10.1111/j.1365-2125.1984.tb02368.x
|View full text |Cite
|
Sign up to set email alerts
|

Desipramine pharmacokinetics in Chinese and Caucasian volunteers.

Abstract: In order to better define the role of pharmacokinetic variation in reported cross‐ethnic differences in dosing patterns of some psychoactive drugs, single dose kinetics of the tricyclic antidepressant desipramine (DMI) were studied in 14 Chinese and 16 Caucasian healthy volunteers. DMI and 2‐OH‐DMI concentrations were assayed with h.p.l.c. in serial plasma and 24 h urine samples over 5 days following an oral 100 mg dose of DMI. Mean total clearance of DMI (CLDMI) from plasma was significantly (P less than 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Such drugs include diphenhydramine (Spector et al, 1980), desipramine (Rudorfer et al, 1984) and nortriptyline (Kishimoto & Hollister, 1984 (Kalow et al, 1979) and of caffeine (Grant et al, 1983), as assessed by urine metabolite concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Such drugs include diphenhydramine (Spector et al, 1980), desipramine (Rudorfer et al, 1984) and nortriptyline (Kishimoto & Hollister, 1984 (Kalow et al, 1979) and of caffeine (Grant et al, 1983), as assessed by urine metabolite concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Some reported that plasma clomipramine concentrations and drug-related adverse effects were significantly higher among Asians (Pakistani and Indian) compared with white British investigators [49,50]. Others reported that the mean plasma clearance of desipramine was significantly higher among whites than the Chinese even after correcting for body weight [51]. There was no significant difference in half-life or plasma protein binding between the two groups.…”
Section: Pharmacogenetics Of Antidepressantsmentioning
confidence: 80%
“…These kinds of studies could reveal information regarding differences among ethnic groups, relevant to optimal dosing strategies. For example, a number of studies have compared clearance rates and peak plasma concentrations for Asian versus White subjects, with mixed findings (Kishimoto and Hollister 1984;Rudorfer et al 1984;Rudorfer et al 1985). Even less is known about pharmacokinetic response in other minority groups (Sramek and Pi 1996).…”
Section: S Department Of Health and Human Services 2001; Freedenthanmentioning
confidence: 97%